TEMPORALITAS PADA VERBA DALAM BAHASA DANI BARAT - Supardi Supardi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2016)
This study aims to describe the temporality aspect of verbs in the Western Dani Language (WDL) in Papua. The data were from Morfologi Bahasa Dani Barat, a researchreport by Purba, et al. (1994). The temporality was proved by the distributional methodsupplemented by permutation and deletion techniques. The findings show that WDLhas nine verb forms. Those are ones with: 1) a singular subject for the present tense, 2) asingular subject for the recent past tense, 3) a singular subject for the remote past tense, 4)a singular subject for the future tense, 5) a plural subject for the present tense, 6) a pluralsubject for the recent past tense, 7) a plural subject for the remote past tense, 8) a pluralsubject for the future tense, and 9) the habitual present tense. Temporality verb forms areclassified into two groups: eight verbs based on the time an event occurs and one verb ofa habitual event. The nine verbs showing time are distinguished on the basis of singularand plural subjects.